Blood collection under anesthesia, peripheral blood cells, plasma biochemistry, and plasma protein electrophoresis in a living fossil: the Spotted Ratfish (Hydrolagus colliei) - Morón-Elorza, Pablo; David, Hugo; Batista, Hugo; Quina, Vanessa; Baylina, Nuria; Pereira, Nuno (Frontiers in Veterinary Science, 2024)
This report describes the safe and effective handling under anesthesia, blood collection and main clinical pathology values determination for three adult Spotted Ratfish (Hydrolagus colliei) (two males and one female) successfully maintained under human care for more than 20 years. The anesthetic MS-222 diluted in tamponed salt water at 50 ppm provided deep narcosis with mean induction and recovery times of 5 and 20 min, allowing safe handling and blood collection in the three animals sampled. Major leukocyte types were similar to other teleost and elasmobranch species, identifying lymphocytes as the predominant leukocyte (75.5%), followed by the fine eosinophilic granulocytes (10.25%), the coarse eosinophilic granulocytes (9.75%), and a small percentage of monocytes (5.50%). Plasma biochemistry values in this species were like those seen in elasmobranchs, with the highest levels of blood urea nitrogen described in any Chondrichthyes (mean 679.7 mmol/l). Plasma protein electrophoresis analysis in the Spotted Ratfish showed five consistent fractions, like those previously described in other fish species, with a negligible quantity of proteins migrating in the region equivalent to albumin, and with fraction 4 (mean 53.20 %) as the predominant fraction. Despite the limitations imposed by the small sample size and the challenging access to the studied species under human care, this study will shed light on and enhance clinical knowledge regarding Ratfish handling, anesthesia, blood collection, and analysis. It aims to deliver a comprehensive clinical pathology description, presenting valuable data for professionals engaged in the care and management of Chimaerans.